(untitled) (African Journal of Public Administration & Management, 2026)
Mental health is a state of well-being in which an individual realizes their abilities, can cope with normal life stresses, work productively, and contribute to their community — WHO Common Mental Health Issues in Africa: • - Depression and anxiety disorders • - Substance and alcohol use disorders • - Post-traumatic stress (from conflict, poverty, and disaster) • - Burnout and workplace-related stress • - Youth and gender-based mental health vulnerabilities (A 2024 meta-analysis across African countries found that roughly 27–30% of adolescents experience significant psychological distress • WHO reports that African women are twice as likely as men to experience depression, yet men are three to four times more likely to die by suicide